Characterization of active sweet potato-based films containing thymol at different varieties: VitAto and Anggun - Nordin, Norhazirah; Romzi, Nur Alia Syafiqah; Manaf, Yanty Noorzianna; Mohamed Amin Tawakkal, Intan Syafinaz; Ariffin, Siti Hajar; Othman, Siti Hajar; Yusof, Yus Aniza (Elsevier, 2021)
Sweet potato starch (SPS) films from local Malaysia varieties particularly, VitAto (orange-fleshed) and Anggun (purple-fleshed) were developed to characterize the physical, mechanical, thermal, and antimicrobial properties. The SPS films were fabricated by solvent casting technique, incorporating different types and concentrations of plasticizer including sorbitol (S) and glycerol (G) at 0, 15, and 30 % of starch. The VitAto SPS films exhibited higher brightness and lower solubility in water than the Anggun SPS films. The plasticized SPS films with 15 % plasticizer demonstrated better tensile strength (TS) and elongation at break (EaB) than the films containing 30 % plasticizer. For the plasticized VitAto SPS films at 15 % loading, the glycerol and sorbitol-plasticized films demonstrated better mechanical and thermal properties than the plasticized Anggun SPS films. The addition of 5 % thymol into SPS films increased the film solubility in water and improved the EaB, while the TS was reduced remarkably. Functional chemical analysis confirmed the presence of intermolecular interaction between the film’s components. The SPS films with thymol showed positive inhibition against Staphylococcus aureus and Escherichia coli in liquid media. Qualitative observations revealed that the active SPS films was able to reduce the growth of fungal on cherry tomato samples and retained the firmness of the food sample. The active SPS films have the potential to be used in food packaging in order to prolong the shelf life of perishable food products.